2009
DOI: 10.1080/17435390902725948
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond particles induce I1-8 expression through a transcript stabilization mechanism in human airway epithelial cells

Abstract: Nanodiamond particles (NDP) prepared by detonational processes have a number of industrial and analytical applications. Previous in vitro studies have reported NDP to be biologically inert with negligible cytotoxicity, implying that they are potentially suitable for novel drug delivery applications. Separate studies, however, have shown that elemental carbon particles, a material closely related to NDP, can induce inflammatory responses in the lung. To assess the potential toxicity of exposure to NDP, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This interleukin is known to be sensitive to changes in redox potential containing an ARE-like element in its promoter region (Zhang et al, 2005). The molecular basis of Nrf2- mediated IL-8 production has been reported to be mainly through enhanced mRNA stability (Silbajoris et al, 2009; Zhang et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
“…This interleukin is known to be sensitive to changes in redox potential containing an ARE-like element in its promoter region (Zhang et al, 2005). The molecular basis of Nrf2- mediated IL-8 production has been reported to be mainly through enhanced mRNA stability (Silbajoris et al, 2009; Zhang et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
“…HMOX1 expression is regulated tightly at the transcriptional level by the Kelch‐like ECH‐associated protein 1/nuclear erythroid 2‐related factor 2/antioxidant response element (KEAP1/Nrf2/ARE) pathway, which is induced by cellular exposure to a broad variety of electrophilic and oxidative stressors [Buendia et al, ; Lambros and Plafker, ; Loboda et al, ]. We have shown previously that exposure of human airway epithelial cells to environmental electrophiles found in ambient air induces the expression of HMOX1 through an oxidant dependent mechanism [Silbajoris et al, ; Cheng et al, ; Wages et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…We designed the oligonucleotides using a primer‐design program (Primer Express, Applied Biosystems) obtained from Integrated DNA Technologies (Coralville, IA). We normalized the data to β‐ACTIN mRNA levels [Silbajoris et al, ; Cheng et al, ; Wages et al, ], which were not found to change in response to treatment with the oil‐burn extract.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it was shown to be either a minor or a transient effect as there were no significant alterations in downstream biological factors observed and one of the author's explanation concerns the highly sensitive cell model that was used in their research. An increase in inflammatory gene expression was found in human lung cells, suggesting the capability of NDs to cause an inflammatory response …”
Section: In Vitro Biocompatibilitymentioning
confidence: 98%